Proses legislasi desa dalam dinamika otonomi desa: Village legislation process in the dynamics of village autonomy - A. Molang Chaerul Kambau; Harsya Harun; Zulkifli Darwis; Budiman Budiman (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2024)
This research aims to understand the process of village legislation in the dynamics of village autonomy, with the locus of the process of forming village regulations, especially the formation of village development plan regulations. Research in Luwu Regency, with a sample of 18 villages from 3 selected sub-districts, which geographically are located on average above 100 m above sea level and quite far from the center of the Regency Capital. Data analysis using a mix method. The research results show that quantitatively the village legislation process with the variable actor involvement in the village legislation process has a significantly positive influence on the village legislation process with a significance value of 0.000<0.05. The activeness variable shows that there is no significant influence on the village legislative process (significance value 0.347> 0.05). Meanwhile, on the competency variable there is a significant influence with a value of 0.027<0.05. This shows that an active role does not make a positive contribution to the village legislative process, which can reflect the representation of community aspirations. The village legislation process (formation of village development plan regulations) in the sample consists of; initiation stage; socio-political stage, and juridical stage.